PUBLIC PERCEPTION AND PRACTICES REGARDING HELMET USE IN PREVENTING HEAD INJURIES IN PESHAWAR, KPK, PAKISTAN: A CROSS-SECTIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Background: Motorcycles are a common and affordable means of transport in Pakistan, but riders face high risk of road traffic accidents and head injuries. Helmet use is the most effective preventive measure; however, compliance remains low despite legal enforcement.Objective: This study aimed to assess public perceptions and practices regarding helmet use in preventing head injuries in Peshawar, Khyber Pakhtunkhwa.Methods: A descriptive cross-sectional study was conducted among 385 participants using convenience sampling. Data were collected through a structured, validated questionnaire evaluating perceptions and practices of helmet use. Descriptive and inferential statistics were applied for analysis.Results: Most respondents recognized helmets as protective and acknowledged their legal requirement. Despite this, practice was poor: the majority reported not carrying or regularly wearing helmets, with many admitting they only used helmets in the presence of traffic police to avoid fines. While 81% of participants had received some form of education on helmet safety, more than half cited discomfort and inconvenience as major barriers to consistent use.Conclusion: A clear gap exists between positive perceptions and poor practices of helmet use. Public awareness campaigns, stronger law enforcement, and addressing practical barriers to helmet compliance are crucial for improving road safety and reducing head injury–related morbidity and mortality.